x-3/7=2/3*3/2x-9/14*2/3

Simple and best practice solution for x-3/7=2/3*3/2x-9/14*2/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-3/7=2/3*3/2x-9/14*2/3 equation:



x-3/7=2/3*3/2x-9/14*2/3
We move all terms to the left:
x-3/7-(2/3*3/2x-9/14*2/3)=0
We can not solve this equation

See similar equations:

| 1.8x-x=46.5574+0.16 | | 5.3+x=55.4 | | 2(x+5)=6x-26 | | 1.8x-x=9.0664+0.16 | | 0=10500-400x+3x^2 | | 0=10500-400+3x^2 | | -14=-4u+2(u+3) | | 1/7(14−7p)−2=−2(12p+3)+6 | | f(4)=F-4-7+3 | | 1.8x-x=0.2+0.16 | | f(4)=4-7+3 | | 7u+4=9u | | 5m+7/2=−2m+5/2 | | 2x=(360/9) | | x*1.8-0.2-x-0.16=0 | | -7/3w=28 | | 5-2z=3z-72+25 | | 3w=-6/5 | | 2x+50=4x+25 | | -3/2u=18 | | x*1.8=0.2+x+0.16 | | 2/5)x-2)=-3 | | 7.5x=400 | | 3(4x+5)=33= | | 7.75x=400 | | 3(4x+5=33)= | | 7.75x=300 | | .02+.07(1-x)=3.5 | | 2/3=y+6 | | 2/3=y+y | | 4(3x-1)=20= | | 2.5n+-3=10 |

Equations solver categories